Trends of Rainfall and Temperature in Bangladesh: A Comparative Analysis of CMIP5 Results and Meteorological Station Data (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
The Coupled Model Inter-comparison Project phase 5 (CMIP5) dataset along with rainfall and temperature data, recorded at 34 stations of Bangladesh Meteorological Department (BMD), is analyzed to examine the recent changes in rainfall and temperature over Bangladesh during the period 1981-2019. In the historical period, all three CMIP5 models (MPI-ESM-LR, MPI-ESM-MR and NorESM1-M) underestimated the observed mean rainfall data collected from BMD, whereas for temperature the result is found to be nearly similar between model and observation. The result shows a trend of increasing mean maximum temperature of Bangladesh at a rate of 0.19°C and 0.26°C per decade and increasing mean minimum temperature at a rate of 0.18°C and 0.15°C per decade, for model and observation respectively. The study found a decreasing trend of annual rainfall in Bangladesh observed at a rate of 41.60 mm and 39.77 mm per decade, respectively, for model and observation. Spatial distribution shows an increase in annual rainfall in the northeastern part of Bangladesh.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(2), 2020, P 9-18